Time synchronization system of Baikal-GVD. (6th September 2021) - Allakhverdyan, V.A.; Avrorin, A.D.; Avrorin, A.V.; Aynutdinov, V.M.; Bannasch, R.; Bardačová, Z.; Belolaptikov, I.A.; Borina, I.V.; Brudanin, V.B.; Budnev, N.M.; Dik, V.Y.; Domogatsky, G.V.; et al.
Abstract: The Baikal-GVD neutrino telescope currently consists of 8 clusters of 288 optical modules (photodetectors). One cluster comprises 8 strings, each of which is subdivided into 3 sections of 12 optical modules. This paper presents the methods of time synchronization between the different GVD components (optical modules, sections, clusters) and estimations of time synchronization accuracy.